Belarus : a perpetual borderland - Savchenko, Andrew (Leiden ; Boston : Brill, 2009)
The book explains Belarusa (TM)s adherence to Soviet social, political and economic institutions. Comparative historical analysis spans the period from the 16th century to the present. Discussion concentrates on development of Belarusa (TM)s national institutions in interaction with Russia and other neighbors.
Foreword and Acknowledgments; Introduction. Images, Concepts and History of a Borderland; Chapter One. The Making of a Borderland; Chapter Two. Ex Oriente Lux: the Belarusian National State and the Soviet Union; Chapter Three. Borderland Forever: Modern Belarus; Conclusion. Whither Belarus?; Bibliography; Index.
Includes bibliographical references (pages 231-235) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Belarus -- History; Belarus -- Politics and government; Belarus -- Economic conditions; Biélorussie -- Histoire; Biélorussie -- Politique et gouvernement; Biélorussie -- Conditions économiques.; HISTORY; Economic history; Politics and government; Belarus; Grenzgebiet; Politik; Belarus; Sociale structuur; Politieke situatie; Economische situatie; Wit-Rusland.; Politik; Grenzgebiet; Weissrussland; Geschichte; History